Community Nurse Practitioner’ Role in Caring Family Caregivers of Bedridden Patients - Fongkerd, Suriya; Sinsuesatkul, Sunun; Tantalanukul, Seubtrakul (Journal of The Royal Thai Army Nurses, 2020)
Caregiving to bedridden patients in family is set to become a major problem in future. As a family member who must to take a role of “Caregiver” for fulfilling the need of patient care at home. The data interviewing Caregives, in this article retrived from Suriya Fongkerd’study. It was called “The Self-Health Care Experiences Of Caregiver’s Older Adults With Bedridden Patients” (Suriya Fongkerd, 2019) The result found that caregivers must go for jobs to earn their living. Most of the times, caregivers at home and exclusive responsibilities lead to accumulative stress and deterioration of caregivers’ health as well. The effect of deterioration of caregivers’ health will affect the quality of care for bedridden patients. Therefore, bedridden caregivers are at risk that health personnel should pay attention and take into account. In this article, the author presents the factors that cause burn out caregivers. The effects of burn out caregivers will negatively affect bedridden patients. To understand the context of the burden caregivers who have direct experiences and stating fatigue, It is a challenge for community nurse practitioners who play a role as health promotion, support and management of health problems for both caregivers and patients who had limited care.